2016
DOI: 10.1175/jcli-d-15-0512.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Interannual Variations of the Energy Flux Equator and ITCZ. Part I: Zonally Averaged ITCZ Position

Abstract: In the zonal mean, the ITCZ lies at the foot of the ascending branch of the tropical mean meridional circulation, close to where the near-surface meridional mass flux vanishes. The ITCZ also lies near the energy flux equator (EFE), where the column-integrated meridional energy flux vanishes. This latter observation makes it possible to relate the ITCZ position to the energy balance, specifically the atmospheric net energy input near the equator and the cross-equatorial energy flux. Here the validity of the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
175
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(190 citation statements)
references
References 39 publications
12
175
1
2
Order By: Relevance
“…Using reanalysis data, we have recently shown that the zonal-mean EFE and ITCZ position covary on seasonal and interannual time scales and that seasonal and interannual variations of the ITCZ position can be quantitatively related to variations of the AET and its derivatives (Adam et al 2016). In the present paper, we examine the relation between the zonally varying EFE and ITCZ and extend the theoretical framework developed for zonal-mean variations Schneider 2014, 2016;Schneider et al 2014;Adam et al 2016) to regional variations.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…Using reanalysis data, we have recently shown that the zonal-mean EFE and ITCZ position covary on seasonal and interannual time scales and that seasonal and interannual variations of the ITCZ position can be quantitatively related to variations of the AET and its derivatives (Adam et al 2016). In the present paper, we examine the relation between the zonally varying EFE and ITCZ and extend the theoretical framework developed for zonal-mean variations Schneider 2014, 2016;Schneider et al 2014;Adam et al 2016) to regional variations.…”
Section: Introductionmentioning
confidence: 77%
“…Usually, an ITCZ and EFE north of the equator imply southward AET across the equator, away from the ITCZ, and vice versa. Indeed, the zonal-mean position of the ITCZ was found to be closely related to cross-equatorial AET in observations (e.g., Donohoe et al 2013Donohoe et al , 2014Adam et al 2016) and in climate models of varying complexity (e.g., Chiang and Bitz 2005;Broccoli et al 2006;Yoshimori and Broccoli 2008;Kang et al 2008Kang et al , 2009Donohoe et al 2013Donohoe et al , 2014.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…[49][50][51] Thus, expanding the zonal-mean energetics framework to two horizontal dimensions is required for predictions of regional rainfall changes in the tropics, say by accounting for the zonal component of divergent AET. 46,52 The application of the energetics framework is further complicated by ocean dynamical feedback. When the ocean circulation is allowed to respond (i.e., O is no longer fixed in Eq.…”
Section: Limitations and Ways Forwardmentioning
confidence: 99%